Implementasi Program Ujian Nasional Di SMA Negeri - Chatarina Sitoresmi Triwiniastuti; Wahyu Sabatini (Universitas Kristen Satya Wacana, 2019)
This study aims to describe how communication, resources, bureaucratic structure and disposition in Ujian Nasional (National Examination) (UN) program implementation. The research approach is qualitative with triangulation analysis techniques and source triangulation. Data collection is done by interview, document study, and observation. Data analysis techniques include data reduction, data presentation, and conclusions. The subjects were principals, vice principals and proctors or technicians at SMA Negeri 1 Pabelan. The results showed that communication, resources, bureaucratic structure and disposition in SMA Negeri 1 Pabelan affected the UN program implementation. The conclusion: there is clear communication between the government and schools through workshops; availability of resources in the form of rules, human resources and adequate infrastructure; bureaucratic structure consists of committees compiled from the central and school levels and there are SOPs in the form of POS UN as guidelines for implementing the National Examination; the attitude of the implementer/disposition has the desire to implement policies with various attitudes in implementing the UN program. Keywords:, ,